2006
DOI: 10.1111/j.1445-2197.2006.03941.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Specimen Ultrasound and Mammography in the Prediction of Tumour‐free Margins

Abstract: Intraoperative specimen ultrasonography is useful in predicting histologically tumour-free margins during breast conserving surgery for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…They considered 4 mm as the minimal tumor-margin distance measurable using their US equipment (9). However, in our series, as reported in previous studies, we used a threshold of 10-mm in order to reduce the false negative rate (12,13,21).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…They considered 4 mm as the minimal tumor-margin distance measurable using their US equipment (9). However, in our series, as reported in previous studies, we used a threshold of 10-mm in order to reduce the false negative rate (12,13,21).…”
Section: Discussionmentioning
confidence: 81%
“…Several studies supporting the use of surgical specimen US have been reported in this field (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimen radiography is mandatory for resection of nonpalpable tumors and can give valuable information on tumor margins [17,18]. Ultrasound can be used with good results as well [19]. Imprint cytology of the surfaces of the specimen is also promising [20,21].…”
Section: What Is a Free Margin?mentioning
confidence: 99%
“…Under routine conditions, the radiologist also has the option of performing specimen ultrasound whenever a lesion is poorly visualized on the radiographs. Ultrasound may be especially useful for evaluating resection margins when a lesion contains no calcifications [17]. If ultrasound is not helpful, the pathologist should be consulted.…”
mentioning
confidence: 99%